2017
DOI: 10.1080/08941939.2017.1400133
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on “Assessment of Risk Factors of Intrauterine Adhesions in Patients with Induced Abortion and the Curative Effect of Hysteroscopic Surgery”

Abstract: Intrauterine adhesions after induced abortion and hysteroscopic surgery 91A. D. S. Sardo et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…This suggests that prior induced abortion did not influence ovulation or ovarian function. In accordance with many previous studies, the data indicated that the spontaneous abortion rate was higher and endometrial thickness was thinner among women with a history of induced abortion. Surgical abortion could make the endometrium thinner by damaging the lining, altering the secretion of inflammation factors, thereby interfering with the bonding between the uterus and embryo, leading to higher rates of spontaneous abortion.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that prior induced abortion did not influence ovulation or ovarian function. In accordance with many previous studies, the data indicated that the spontaneous abortion rate was higher and endometrial thickness was thinner among women with a history of induced abortion. Surgical abortion could make the endometrium thinner by damaging the lining, altering the secretion of inflammation factors, thereby interfering with the bonding between the uterus and embryo, leading to higher rates of spontaneous abortion.…”
Section: Discussionsupporting
confidence: 91%
“…Mo et al retrospectively analyzed factors influencing IUA and found age and BMI were not influencing factors, but female genital tract inflammation, an excessive number of pregnancies, history of intrauterine surgery [curettage, negative pressure suction, and cesarean section (22,23) were. Others have pointed out that more than two intrauterine operations, a curettage time of more than 15 minutes, and a history of myoma of uterus and polyps were also harmful factors (24,25). Chen et al further conducted an in-depth study on patients with secondary infertility and found that the number of abortions and surgical methods were not risk factors for secondary infertility after induced abortion, but IUA, endometritis, chronic salpingitis, ovarian dysfunction, and endometriosis were (26).…”
Section: Symptoms and Risk Factors Of Intrauterine Adhesionsmentioning
confidence: 99%